The analysis of the threshold value of the complex short-circuit ratio index and its significance in the context of static voltage stability - Lei, Pan; Zhao, Jinquan (Frontiers in Energy Research, 2024)
The short-circuit ratio index(SCR) can effectively quantify the voltage support strength in traditional DC grid-connected scenarios, yet it cannot reasonably describe the voltage support strength in diverse device grid connection scenarios. This paper introduces a new calculation method of the complex short-circuit ratio index(  SCR ) and derives the threshold value of the complex short-circuit ratio index to enable a comprehensive quantitative assessment of grid voltage support strength across diverse device grid connection scenarios. Firstly, critical short-circuit ratio(CSCR) under different assumed conditions were derived based on the short-circuit ratio index. Secondly, the calculation method of the complex short-circuit ratio index was introduced, considering both the equivalent impedance angle of the device and the Thevenin equivalent impedance angle. This was followed by the determination of the threshold value of the complex short-circuit ratio(  CSCR ), enabling a precise quantitative evaluation of power grid voltage support strength in diverse device grid connection scenarios. Finally, the example analysis proves the accuracy and efficacy of the complex short-circuit ratio index in assessing the voltage support strength of diverse devices in grid-connected scenarios.